2019
DOI: 10.1186/s12885-019-6281-1
|View full text |Cite
|
Sign up to set email alerts
|

Red blood cell distribution width and platelet counts are independent prognostic factors and improve the predictive ability of IPI score in diffuse large B-cell lymphoma patients

Abstract: Background: Elevated red blood cell distribution width (RDW) and decreased platelet count (PLT) can be clinically relevant to the prognosis in cancer patients. However, their prognostic values in patients with diffuse large B-cell lymphoma (DLBCL) need to be further explored. Methods: Healthy donors (n = 130) and patients with DLBCL (n = 349) were included and evaluated retrospectively in this study. The prognostic influence of clinical and pathological factors including RDW and PLT on overall survival (OS) an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
32
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(37 citation statements)
references
References 48 publications
2
32
3
Order By: Relevance
“…In the last studies, it was found that the decreased PLT level predicts a worse prognosis in lymphoma patients (10,21,22). In our study, there was a statistically significant relationship between the PLT level and mortality in patients with NHL and our study showed that the low PLT level in NHL patients indicates a worse survival rate, but no significant correlation was found between the PLT level and mortality and OS in patients with HL.…”
Section: Discussioncontrasting
confidence: 42%
“…In the last studies, it was found that the decreased PLT level predicts a worse prognosis in lymphoma patients (10,21,22). In our study, there was a statistically significant relationship between the PLT level and mortality in patients with NHL and our study showed that the low PLT level in NHL patients indicates a worse survival rate, but no significant correlation was found between the PLT level and mortality and OS in patients with HL.…”
Section: Discussioncontrasting
confidence: 42%
“…35,37 However, these findings were denied in other studies. 19,36,38,39 In our analysis, we found that thrombocytopenia but not anaemia was associated with BM involvement. These inconsistent findings might result from the different cut-off values of BM involvement of lymphoma cells.…”
Section: Discussionmentioning
confidence: 48%
“…RDW has also been found to be a prognosticator in a wide variety of cancers [37][38][39]. Where RDW has already gained prognostic value in predicting overall survival in patients with glioblastoma [18], the ratio formed from it together with platelet count (RPR) is experiencing increasing interest in other diseases [12,13,40,41]. Platelet count as such is of unsteady predictive value.…”
Section: Discussionmentioning
confidence: 99%
“…This is due to the fact that the normal distribution of platelet counts contains a range and not a cut-off value, so that the individually adjusted cut-off values in the individual studies are not comparable. In glioblastoma, an increase in platelet count was previously assumed to be an unfavorable prognostic feature [ 41 ]. This fits with the experience in most solid tumors that the elevated platelet count plays a critical role in progression and metastasis [ 42 44 ].…”
Section: Discussionmentioning
confidence: 99%